Hastaneye Yatış Gerektiren Toplum Kökenli Pnömoni Olgularında Mortalite Oranı ve Etkileyen Faktörler - Kuluöztürk, Mutlu; Eser, Gülden; Ağaoğlu, Gökçen; Deveci, Figen (İstanbul Aydın Üniversitesi, 2021)
Aim: To determine the mortality rate and affecting factors in patients with community-acquired pneumonia (CAP) requiring hospitalization. Method: 150 patients with CAP retrospectively evaluated. Age, gender, hospital mortality, presence of concomitant disease, smoking history, history of intensive care unit and invasive mechanical ventilation, hospitalization time, arterial oxygen saturation (SaO2), CURB-65 score, sputum culture results, values of pulse, arterial blood pressure, fever, respiratory rate, confusion status, hemogram, urea, creatinine, CRP and procalcitonin (PCT) values were recorded from our hospital’s database system. Results: The hospital mortality rate was 12.7% (n = 19). The mean age, CURB65 scores, fewer, respiratory rate, neutrophil counts, urea, CRP levels and PCT positivity were statistically increased and SaO2 levels, systolic TA, diastolic TA, lymphocytes and platelet counts were statistically decreased in CAP patients with died in-hospital. Logistic regression showed that need for invasive mechanical ventilation, confusion status and PCT positivity were significantly associated with in-hospital mortality. Conclusion: Advanced age, high neutrophil ratio, high CURB-65 score and low systolic TA values are related factors with hospital mortality in patients with CAP requiring hospitalization. In addition, invasive mechanical ventilation, confusion status and PCT positivity are independent risk factors for hospital mortality in CAP patients.
Keywords: Clinical Sciences; Klinik Tıp Bilimleri